Chinese massage therapy (Tuina) inhibits motor neuron apoptosis in rats with sciatic nerve injury by regulating the cPLA2 and RhoA/ROCK2 signaling pathways - Jiawei Sun; Yingqi Zhang; Zhifeng Liu; Hanyu Zhang; Jiayue Liu; Yue Xu; Rentuya Na; Hongzheng Zhang; Jiawang Yan; Tianyuan Yu (Frontiers in Neurology, 2025)
ObjectiveTo investigate whether Tuina therapy alleviated inflammation and motor neuron apoptosis in sciatic nerve injury (SNI) rats by regulating cytosolic phospholipase A2 (cPLA2) and Ras homolog family member A/Rho-associated coiled-coil comprising protein kinase 2 (RhoA/ROCK2) signaling cascades.MethodsFour experimental cohorts were established utilizing 36 male Sprague–Dawley rats: control, sham, SNI, and TUI. We implemented a sciatic nerve injury (SNI) model. At dthe mid-thigh level, sciatic nerves were exposed and crushed for 5 s using non-serrated forceps at points spaced approximately 2 mm apart. Postoperatively, Tuina therapy (Chinese therapeutic massage, Tuina) was administered to evaluate its neuromodulatory effects. SNI models were established in the SNI and TUI cohorts. TUI cohorts applied with “Three-Manipulation and Three-Acupoint” technique, which included pressing, plucking, and kneading on the acupoints Yinmen (BL37), Chengshan (BL57), and Yanglingquan (GB34). The control cohort underwent no intervention. The sham surgery and model cohorts underwent restraining interventions. Motor function was assessed using Basso, Beattie, and Bresnahan (BBB) scores and CatWalk gait analysis. Spinal cord (SC) histology was evaluated using hematoxylin and eosin and Nissl staining. NeuN-positive cells were quantified via immunofluorescence. Tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and aquaporin-4 levels were determined through enzyme-linked immunosorbent assay. RhoA, ROCK2, Bax, Bcl-2, and cPLA2 mRNA levels were analyzed using real-time quantitative polymerase chain reaction. RhoA, ROCK2, Bax, Bcl-2, cPLA2, and p-cPLA2 protein expressions were analyzed using western blotting to investigate the impact of Tuina therapy on nerve regeneration and apoptosis regulation.ResultsThe TUI cohort showed better BBB scores and CatWalk results than the SNI cohort (all p < 0.001). Histological analysis revealed diminished inflammatory cell infiltration and increased neuronal survival. NeuN immunofluorescence indicated decreased motor neuron apoptosis in the anterior horn of the SC. Tuina therapy reversed TNF-α, IL-6, and aquaporin-4 levels (p < 0.01). The TUI cohort had lower mRNA expression of Bax, cPLA2, and ROCK2 (all p < 0.001), mRNA expression of RhoA (p < 0.01), and Bax, cPLA2, p-cPLA2, and RhoA/ROCK2 levels (all p < 0.001) than the SNI cohort. Conversely, mRNA and protein expression levels of Bcl2 were higher in the TUI cohort than in the SNI cohort (all p < 0.001).ConclusionTuina therapy improved motor function in SNI rats by inhibiting motor neuron apoptosis via cPLA2 regulation, potentially via the RhoA/ROCK2 signaling pathway.